ANALYSIS OF HYDRODYNAMIC JOURNAL BEARING WITH AN AXIAL GROOVE - MOHAMMAD PURE, SHAHAB HAMDAVI (2017)
In rotordynamic, hydrodynamic journal bearings are one of the most crucial components due to their wide demand and applications in different industries ranging from small applications, such as those supporting rotating grinders for dentistry, to large applications, like supporting generators, steam turbines, etc. Meanwhile, stability of this kind of bearings is an essential issue and lack of appropriate design can lead to instability and undesirable vibration in the rotor-bearing systems. Surface texturing is a widely-used technique and is reported by other researchers as an appropriate way to improve static and dynamic properties and stability parameters of the hydrodynamic journal bearings. The aim of this work is to study the effects of three parameters namely groove depth, groove width, and eccentricity ratios on the linear stability of rigid rotor-bearing systems supported by two symmetric grooved hydrodynamic journal bearings. To do so, static and dynamic characteristics as well as stability parameters of the grooved hydrodynamic journal bearing need to be investigated. This investigation was conducted when a single axial groove as a subgroup of the surface texturing technique is applied to the bearing surface in the full film region. The range of case studies in this research work are limited to three groups of long, finite-length, and short hydrodynamic journal bearings. The governing equation is Reynolds equation in which three proper theories of Reynolds, finite difference method, and short bearing approximation are applied to the long, finite-length, and short journal bearings, respectively, to ease the numerical procedure. The applied groove resulted in different effects on the considered bearings. For instance, long and finite-length grooved bearings enjoy higher load-carrying capacities compared to plain bearing by 97.90% and 47.63%, respectively. Nevertheless, it cannot be a good option for static coefficients of a short journal bearing, whereby all results for grooved bearings are lower compared to plain bearing. Besides, from a stability point of view, long and short bearings with eccentricity ratios higher and lower than 0.3, respectively, are operating in the stable region. Nonetheless, the finite-length bearing does not operate at stable region and in the best condition operates on threshold contour line for eccentricity ratios higher than 0.5.